The Influence of Influencer Marketing on the Interest in Purchasing MSME Products in Southeast Aceh - Roezaini Soefi; Nasruddin Nasruddin; Sopira Qori Amalia (Cahaya Abadi Publisher, 2026)
This study aims to analyze the influence of influencer marketing on the purchase intention of MSME products in Southeast Aceh Regency. Amidst the aggressive internet penetration in Aceh Province, reaching 90%, local MSME actors still face challenges in transforming conventional promotional strategies into digital platforms. Using a quantitative approach, data were collected through questionnaires from 100 respondents selected via purposive sampling. Data analysis was conducted using simple linear regression through SPSS software. The results show that influencer marketing has a positive and significant effect on purchase intention (p < 0.05), with a coefficient of determination (R 2 ) of 0.526. This indicates that 52.6% of the variability in consumer purchase intention in Southeast Aceh is triggered by the credibility and attractiveness of public figures on social media. These findings confirm that collaboration with local influencers who understand regional authenticity values is a crucial strategy to expand MSME market access in buffer zones. The practical implications suggest that local governments and business actors strengthen the digital marketing ecosystem through community-based branding training.